The artistic creation of cultural sustainability and interactive creativity through three-dimensional animation / Zhao Jie ... [et al.] - Jie, Zhao; Dalal, Sanghamitra; Abu Bakar, Mohd Syuhaidi; Wan Yahaya, Wan Aida (College of Creative Arts, 2024)
In the evolving spectacle of artistic expression, three-dimensional (3D) animation has emerged as an important medium offering dynamic illusions for cultural sustainability and interactive creativity. This article explores the integration of technology and art, particularly focusing on the 3D animation for the Chinese zodiac as new media for traditional cultural symbols which cultivates a sustainable humanistic heritage in a digital age. The CG illustration of this zodiac character utilizes a 3D animation tool namely Blender, which is open-source software for individual artists and micro studios. The interactive 3D animation art is a creative form and theoretical extension of media spectacle. The behaviour of the participants in interactive animation affects the plot and meaning of the artwork. Interaction and interference work mutually in the media spectacle. Concurrently, the rise of Artificial Intelligence in Generative Content (AIGC) introduces a dilemma offering diversity and innovation, while simultaneously challenging established aesthetic norms and disrupting conventional production processes. The anticipated results promise to contribute significantly to the realm of 3D animation art, fostering cross-cultural understanding and interactive communication.